Development of bacterial mixtures for removal of refractory pollutants in anaerobic wastewater treatment - Kang, Ken Kee Keng (2014)
Anaerobic treatment of wastewater is advantageous over aerobic treatment due to its low processing cost and production of useful methane biogas. However, industrial pollutants such as Pentachlorophenol (PCP) are hard to remove and may result in toxicant overload, reducing performance of the treatment process. Bioaugmentation, an approach involving the addition of specific microbial strain or consortia to the indigenous community may alleviate such toxicity. In this study, we aimed to develop a preliminary consortium to degrade PCP via the reductive dehalogenation pathway. Several batch-scale bioreactors, containing sludge obtained from local wastewater treatment plant, were set up and exposed to different metabolites of PCP biodegradation. Liquid culture dilution assay (LCDA) was done to reduce the complexity of these sludge, obtaining a simplified group of "specialist" strains. Sub-culturing was done to increase the volume of selected groups of "specialist" strains for testing of refractory compound reduction via high-performance liquid chromatography (HPLC). The consortia were then generated via mixing of these subcultures. Results showed the consortia were able to reduce PCP concentration by 66%. Solid culture dilution assay (SCDA) was also done to isolate potential refractory compound degraders. A total of 15 colonies were identified as potential Tier 1 degraders with a refractory compound reduction of more than 40%. Characterisation of isolates by general morphology and ability to grow on different carbon sources were done to obtain information that may be useful for future application of isolates.